2021
DOI: 10.1002/solr.202100882
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Organic Semiconductors as Hole Transport Layers in p–i–n Perovskite Solar Cells

Abstract: Thin polymeric and small‐molecular‐weight organic semiconductors are widely employed as hole transport layers (HTLs) in perovskite solar cells. To ensure ohmic contact with the electrodes, the use of doping or additional high work function (WF) interlayer is common. In some cases, however, intrinsic organic semiconductors can be used without any additive or buffer layers, although their thickness must be tuned to ensure selective and ohmic hole transport. Herein, the characteristics of thin HTLs in vacuum‐depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…The performance of perovskite solar cells is influenced by several factors, such as the fabrication atmosphere, device configuration, and charge transporting layers. [ 40–45 ] Therefore, a direct comparison between our results and those reported in the literature may not be suitable. However, it is evident that the performance of the cell in our study can compete with those reported in the literature, indicating that the gas‐quenching approach applied in our study can serve as a viable alternative to the other approaches used in the literature.…”
Section: Resultsmentioning
confidence: 80%
“…The performance of perovskite solar cells is influenced by several factors, such as the fabrication atmosphere, device configuration, and charge transporting layers. [ 40–45 ] Therefore, a direct comparison between our results and those reported in the literature may not be suitable. However, it is evident that the performance of the cell in our study can compete with those reported in the literature, indicating that the gas‐quenching approach applied in our study can serve as a viable alternative to the other approaches used in the literature.…”
Section: Resultsmentioning
confidence: 80%
“…Devices were built on indium tin oxide (ITO) patterned glass substrates, and a thin (3 nm) layer 2,2",7,7"Tetra(N,Ndiptolyl)amino9,9spirobi fluorene (SpiroTTB) was used as the hole transport layer (HTL), as it can be used as a standalone material without any high work function interlayers at the ITO/HTL interface. [67,68] A 450 nm thick wide bandgap perovskite was evaporated onto the SpiroTTB, and coated with carbon 60 fullerene (C 60 , 25 nm) and bathocuproine BCP (8 nm) as electron transport layers (ETLs). The thickness of the perovskite film was chosen to ensure sufficient current collection, although, with alternative vacuumdeposition methods, much thinner films with similar current collection efficiency have been reported.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, they found that a very thin and undoped film of spiro-TTB (<3 nm) could be used to ensure ohmic contact between the ITO and the MAPbI 3 absorber layer, which produces very efficient solar cells. [47] For example, a PSC employing spiro-TTB as the HTL exhibited a maximum PCE of 19.5% (Figure 6). [48] In a fully textured monolithic perovskite/silicon tandem solar cell (Figure 7a), ITO or hydrogenated nanocrystalline silicon (nc-Si:H) was used as the recombination junction between the bottom and top cells.…”
Section: Copper Phthalocyanine (Cupc)mentioning
confidence: 99%
“…Interestingly, they found that a very thin and undoped film of spiro‐TTB (<3 nm) could be used to ensure ohmic contact between the ITO and the MAPbI 3 absorber layer, which produces very efficient solar cells. [ 47 ] For example, a PSC employing spiro‐TTB as the HTL exhibited a maximum PCE of 19.5% ( Figure ). [ 48 ]…”
Section: Interlayers In Vacuum‐processed Pscsmentioning
confidence: 99%